Mediating role of electronic word of mouth 2.0 in the relationship between digital product quality and purchase intention - Arif, Chairul (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: In 2025, Indonesia’s telecommunications industry is dominated by three major providers using GSM-based technology: TSL, IDT, and PX. During the first quarter of 2025, the subscriber base of these leading operators reached significant numbers, with TSL serving 158.81 million users, IDT 95.4 million, and PX 58.8 million. Combined, these three providers accounted for a total of 348 million subscribers. This intense market landscape has fueled strong competition among prepaid card providers, pushing market players and producers to innovate and implement effective strategies in order to secure a competitive advantage. Methods: The sampling technique employed in this study is the snowball sampling method. For data analysis, the research applies Partial Least Squares (PLS), which represents a variance-based approach to Structural Equation Modeling (SEM). This method allows for the simultaneous testing of both the measurement model and the structural model, thereby providing a comprehensive framework for evaluating complex relationships among variables. Findings: The results of this study demonstrate that both Electronic Word of Mouth (E-WOM) and Product Quality significantly influence Purchase Intention. E-WOM was found to have a positive and significant effect on Purchase Intention (p= 0.00<0.05), indicating that consumers who are exposed to favorable online reviews and recommendations are more likely to purchase. Digital Product also showed a significant effect on E-WOM (p= 0.00<0.05), suggesting that high-quality products encourage consumers to share positive experiences through digital platforms. Furthermore, Digital Product directly affects Purchase Intention in a positive and significant manner (p= 0.009<0.05), confirming that perceptions of product excellence strengthen consumers’ purchasing decisions. Overall, these findings highlight that Digital Product not only directly increases Purchase Intention but also indirectly enhances it through its influence on E-WOM. Conclusion: The results show that Electronic Word of Mouth (E-WOM) has a positive and significant effect on Purchase Intention at TSL. In addition, Digital Product positively and significantly influences both E-WOM and Purchase Intention, confirming that better Digital Product not only encourages customers to share favorable feedback but also directly strengthens their intention to purchase. Novelty/Originality of this article: The novelty aspect refers to the new or innovative elements in a research study that distinguish it from previous work. It includes unique contributions, new methods, or findings that have not been explored before in the field.